19. Integrated Course Delivery Packages - Annis, Judy; Hensel, Tracy; Lundstrom, Patricia; Jones, Richard (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2003)
This report contains updates of three products: Elluminate, LearnLinc, and Wimba. Each features audio communication, both asynchronous and synchronous, and has been selected for this report to complement the preceding review of Internet audio products. The three packages also contain integrated applications for online, classroom-like, educational activities and discussions. A fourth service, Ed2Go, offers online tutorial facilities similar to those provided by the Elluminate vendor. The four reviews are offered as examples of the many products now offering integrated applications of this type.